The Role of Emotion Regulation on Job Stress of Elementary School Teachers/ Peran Regulasi Emosi terhadap Stres Kerja Guru Sekolah Dasar - Prastuti, Endang; Febrinan, Jhodie (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
Abstract: Teaching profession at elementary school level is one of the working sectors that tend to raise job stress; however, the extent to which the role of emotion regulation in describing the job stress of elementary school teachers is still unrevealed.Â This study aims to investigate (1) how is the condition of emotion regulation and job stress on teachers; (2) what is the role of emotion regulation on job stress in teachers; (3) to what extent is the role of emotion regulation on job stress in teachers. The present study used a quantitative approach. Meanwhile, the sampling technique used in this study was incidental sampling which involved eighty-seven elementary school teachers. The measuring instruments used were an Emotion Regulation Questionnaire (9 items; Î± = 0.630) and a Teacher Concerns Inventory (48 items: Î± = 0.968). The data were analyzed using simple linear regression analysis. The results showed that (1) the majority of teachers had very high emotion regulation and had very low job stress, (2) there was a significant negative influence between regulation of emotion and teacher job stress, (3) the emotion regulation contributed 29.2% to teacher job stress.Keywords: Emotion Regulation; Job Stress; Elementary School TeachersAbstrak: Profesi guru di tingkat sekolah dasar merupakan salah satu sektor pekerjaan yang rentan menimbulkan stres kerja, namun belum diketahui sejauh mana peran regulasi emosi dalam menjelaskan stres kerja guru SD. Tujuan penelitian ini untuk mengungkapkan (1) Bagaimana kondisi regulasi emosi dan stres kerja pada guru; (2) Bagaimana peran regulasi emosi terhadap stres kerja pada guru; (3) Seberapa besar peran regulasi emosi terhadap stres kerja pada guru. Penelitian ini menggunakan pendekatan kuantitatif. Teknik pengambilan sampel dalam penelitian ini menggunakan teknik incidental sampling. Subjek penelitian berjumlah 87 guru sekolah dasar. Alat ukur yang digunakan adalah kuesioner regulasi emosi (9 aitem; Î± = 0.630) dan kuesioner stres kerja guruÂ (48 aitem: Î± = 0.968). Data dianalisis dengan menggunakan analisis regresi linier sederhana. Hasil penelitian menunjukkan bahwa (1) mayoritas guru memiliki regulasi emosi yang sangat tinggi dan memiliki stres kerja yang sangat rendah, (2) terdapat pengaruh negatif dan signifikan antara regulasi emosi terhadap stres kerja guruÂ (3) regulasi emosi memberikan peran sebesar 29.2% terhadap stres kerja guru.Kata Kunci: Regulasi Emosi; Stres Kerja; Guru Sekolah Dasar